REFERENSI INTERLOKUTOR DALAM PERCAKAPAN PADA PODCAST CLOSE THE DOOR - Adi Imam Taufik; Filia (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
This study examines interlocutor reference in conversation on Close the Door podcast hosted by Deddy Corbuzier. The data search of this research consist of 116 instances of interlocutor reference. The theory used in this paper is the address terms proposed by Brown and Gilman (1960) as well as Sign of Deference, Sign of Demeanour; Interlocutor Reference and Self-Other Relation written by Dwi Noverini Djenar (2022). The aim of the study is to describe interlocutor reference in coversation on the podcast. Based on initial observations, it appears that the interlocutor reference used in speech sequences varies. Therefore, further research is needed to provide a picture of interlocutor characterisctics on the podcast. The results show that speaker use polite and familiar interlocutor references for the same conversational partner in the same speech sequence. For example, speakers use interlocutor reference such as Mr. Nadiem makarim, Elu, Bro Bos, and Brother in the same speech sequences. In addition, the use of interlocutor rreference such as Gus, Gus Yaqut, and Andain the same speech sequences was also found. The use of diverse interlocutor references indicates deferential relationship among speakers. Deferential relationship in conversations refer to the strategies used by the speakers to show respect, politeness, and familiarity to their conversational partners.